Analysis of the Suboptimal Performance of the Steering Gear on MT. Narpatisuta - Pangestu, Arfianda Rizki Pangestu (Maritime Park: Journal of Maritime Technology and Society, 2024)
The steering gear is one of the auxiliary machineries on board a ship that is used to move the ship's rudder, allowing the ship to turn to the right or left. This machinery utilizes an electro-hydraulic system, which combines electric and hydraulic technologies to control the ship's steering direction. The research focuses on analyzing the suboptimal performance of the steering gear on the MT. Narpatisuta. The objectives of the research are to identify the factors causing the suboptimal performance of the steering gear, the impacts resulting from this suboptimal performance, and the efforts made to address the suboptimal performance of the steering gear on the MT. Narpatisuta. The research method used is a qualitative descriptive method, with data collection techniques in the form of observation, interviews, documentation and literature study. The data analysis technique uses the SHEL method. Test the validity of the data using triangulation. The research results show that suboptimal performance of the steering gear is caused by hydraulic pipe leaks, deteriorating quality of hydraulic oil, and damage to seal and o-ring components, which lead to reduced steering gear performance, slower rudder movement, and can disrupt ship operations, endangering crew safety and the ship's cargo. Efforts that can be made to remedy this include routine inspection and maintenance of the steering gear and its components. Thus, this research emphasizes the need for routine inspection and maintenance to prevent these problems which must ensure maximum steering gear function, maintain safety and ship operational efficiency.